STUDI LITERATUR TENTANG PERILAKU PROSOSIAL PADA REMAJA - Nurul Fadlah Nasution; Elni Yakub; Arli Rusandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Prosocial behavior is any action taken or planned to help others, regardless of the helper's motives. Prosocial behavior is positive behavior that benefits or makes other people's physical or psychological conditions better, which is carried out on a voluntary basis without expecting rewards. This study aims to determine the development of prosocial behavior in adolescents in Indonesia, to determine the factors that influence adolescent prosocial behavior, forms of prosocial behavior, and efforts to increase prosocial behavior in adolescents. This research is a literature study research. The instrument used in this research is a combination of national and international journals. Data analysis in this study used qualitative. The results showed that among teenagers this prosocial behavior was quite developed because of the efforts made by family, teachers, and peers. This prosocial behavior has been improved in schools where teachers have used services and guidelines in improving this prosocial behavior. Which is in the process of increasing peer group is also one of the factors that influence the development of prosocial behavior in adolescents.Key Words: Literature study, Prosocial behavior